35=x+(2x-1)+(2+14x)

Simple and best practice solution for 35=x+(2x-1)+(2+14x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 35=x+(2x-1)+(2+14x) equation:


Simplifying
35 = x + (2x + -1) + (2 + 14x)

Reorder the terms:
35 = x + (-1 + 2x) + (2 + 14x)

Remove parenthesis around (-1 + 2x)
35 = x + -1 + 2x + (2 + 14x)

Remove parenthesis around (2 + 14x)
35 = x + -1 + 2x + 2 + 14x

Reorder the terms:
35 = -1 + 2 + x + 2x + 14x

Combine like terms: -1 + 2 = 1
35 = 1 + x + 2x + 14x

Combine like terms: x + 2x = 3x
35 = 1 + 3x + 14x

Combine like terms: 3x + 14x = 17x
35 = 1 + 17x

Solving
35 = 1 + 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.
35 + -17x = 1 + 17x + -17x

Combine like terms: 17x + -17x = 0
35 + -17x = 1 + 0
35 + -17x = 1

Add '-35' to each side of the equation.
35 + -35 + -17x = 1 + -35

Combine like terms: 35 + -35 = 0
0 + -17x = 1 + -35
-17x = 1 + -35

Combine like terms: 1 + -35 = -34
-17x = -34

Divide each side by '-17'.
x = 2

Simplifying
x = 2

See similar equations:

| 4x-10+7(x-3)=0 | | 6(2+7x)+3x=9+6(9+8x) | | (2x+4y)+(2x-y)-(x-2y)= | | 16-(3x-15)=4x-(9x-9) | | 3=8x-7x+4 | | y^3(3-4x^2)=7x-y^4 | | 2(x+3/4)=9(1/6-x) | | -8x+9x+6=9 | | 6x-8x+2=-13 | | 35=x+(2x-1)+(3(2x-1)+3) | | 35=x+(2x-1)+(3(2x-1)+2) | | 35=x+(3x-1)+(4(3x-1)+2) | | x(x+5)+1=(x+6)(x+6) | | 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 |

Equations solver categories